Principal Leadership in Implementing Center of Excellence Programs: A Case Study of SMK Mekanika Buntet Pesantren Cirebon, Indonesia - Basri Asyibli; Ahmad Arifi (Islamic Education Management Study Program, Faculty of Tarbiyah and Education State Islamic University (UIN) Sunan Kalijaga Yogyakarta, Indonesia, 2023)
Purpose – This study aims to investigate the role of school principals in implementing the Center of Excellence (CoE) program, aligning with the Ministry of Education and Culture's objectives. Specifically, the research focuses on understanding the principal's leadership style, strategies, and involvement in executing the CoE program at SMK Mekanika Buntet Pesantren Cirebon. Design/methods/approach – Conducted as qualitative field research, this study is situated at SMK Mekanika Buntet Pesantren Cirebon. Data collection involves observation, interviews, and documentation. Data analysis includes data reduction, data presentation, and conclusion to explore the principal's leadership style, strategies, and involvement in CoE program implementation. Findings – The study reveals that the principal at SMK Mekanika effectively implements the CoE program by the Minister of Education and Culture's Decree No. 17/M/2021. This includes the construction of CoE laboratories, productive teacher internships, workshops, post-training monitoring and evaluation, and learning implementation supervised by managerial supervisors. The principal employs a strategy focusing on educator and staff quality enhancement, collaboration with companies, partnerships with universities, and establishing relationships with other CoE-affiliated schools. The principal's leadership role spans educator, manager, supervisor, leader, innovator, and motivator. Research implications/limitations – The research implies the critical role of school principals in successfully implementing the CoE program. Rules include the specific context of SMK Mekanika Buntet Pesantren Cirebon, which may limit generalizability. Practical implications – The findings offer valuable insights for school leaders and policymakers involved in CoE program implementation. Understanding effective leadership styles and strategies can guide other educational institutions in achieving successful CoE initiatives. Originality/value – This research contributes to the literature by exploring the principal's role in executing the CoE program, encompassing leadership styles, strategies, and practical involvement. The study's originality lies in its specific focus on a school context and its potential to inform best practices for successful CoE program implementation in similar educational settings.